Vision Therapy for the Autistic Patient: A Literature Review and Case Report. - Au, Michael; Coulter, Rachel (Optometry & Visual Performance, 2014)
Background: The heightened awareness of autism spectrum disorder (ASD) has propelled concern for proper care into a significant public health issue. Vision deficits, including visual processing and integration, may contribute to the anxiety and uneasiness that these individuals frequently experience. Additionally, these deficits often translate into considerable hindrances to classroom success. This paper addresses a sampling of vision-based behaviors in ASD including visual hyper/hyposensitivity, poor facial recognition, lack of eye contact, and visual-motor integration impairments. Case Summary: A 10-year-old autistic male was referred for diagnosis of convergence insufficiency. There were notable developmental delays and concerns primarily regarding reading comprehension, attention deficits, and spatial organization. He previously received speech and language therapies in conjunction with occupational therapy. Diagnostic testing of the patient's ocular motility yielded tracking inefficiencies and poor accuracy. The Wachs Analysis of Cognitive Structures (WACS) evaluation was performed and revealed weaknesses in a number of visualization tasks as well as in gross and fine motor coordination. An individualized program of vision therapy was recommended to improve his visualization, tracking, and visual motor integration abilities. Conclusion: This case report illustrates how the distinctive challenges of structuring a successful vision therapy program for the varying presentations of ASD can be met by adapting techniques to the appropriate developmental stage of the child. Vision therapy provides the framework to build skills that are transferrable and valuable in the classroom.